ANALISIS KINERJA KEUANGAN PT. ACE HARDWARE INDONESIA, TBK - Kurniati Ningsih; Erni Setiawati; Rudy Syafariansyah (University of Widya Gama Mahakam Samarinda, 2019)
The purpose of this study is to find out and analyze the financial performance of PT. Ace Hardware Indonesia in terms of liquidity, solvency and profitability ratios for the period 2013 to 2017. This research method is descriptive by using financial ratio analysis tools such as liquidity ratio, solvency, and profitability to determine the company's financial performance. From the results of the analysis, it is known that the liquidity ratio has a ratio above the industry average ratio, the solvency ratio has a ratio value below the industry average ratio, and the profitability ratio has a ratio value above the industry average ratio.